Isokinetic strength in female soccer players by player position - Sepúlveda, C.; Fernández, V.; Silvestre, R.; Giancáspero, F.; Aedo-Muñoz, E.; Bustamante-Garrido, A.; Burgos-Jara, C.; Cerda-Kohler, H. (ISBS Proceedings Archive (Michigan), 2023)
This study aimed to establish reference values and compare isokinetic performance in female soccer players according to player position. Eighty-seven female soccer players from the Chilean first-division soccer clubs were evaluated in isokinetic strength. The player position was grouped as goalkeeper (GK), central defender (CD), lateral defender (LD), midfielder (MF), and forward (FW). Concentric knee extension and flexion muscle strength measurements were conducted using a standardized test protocol with an angular velocity of 60º/sec. There were no differences in peak torque of knee extension and flexion between player positions in both the dominant leg (DL) and the nondominant leg (NDL). The H:Q ratio shows significant differences (p=0.0379) in the dominant leg between CD vs. MF (GK: 63.1±11.1; CD: 55.6±4.6; LD: 62.5±9.6; MF: 64.8±12.0; FW: 61.1±10.9). Our results can be used for practitioners working with female professional soccer players to assess and monitor strength according to player position to improve performance. Future studies should confirm whether these values can be used as risk factors, complementing other functional metrics (e.g., eccentric force) and different angular velocities.